The Bible in Arab Christianity - Thomas, David 1948- (The history of Christian-Muslim relations, 2007)
The contributions to this volume, which come from the Fifth Mingana Symposium, survey the use of the Bible and attitudes towards it in the early and classical Islamic periods. The authors explore such themes as early Christian translations of the Bible into Arabic, the use of verses from it to defend the truth of Christianity, to interpret the significance of Islam and to prove its error, Muslim accusations of corruption of the Bible, and the influences that affected production of Bibles in Muslims lands. The volume illustrates the centrality of the Bible to Arab Christians as a source of authority and information about their experiences under Islam, and the importance of upholding its authenticity in the face of Muslim criticisms. Contributors include: Samir Arbache, Mark Beaumont, Emmanouela Grypeou, Lucy-Anne Hunt, Juan Pedro Monferrer Sala, Said Gabriel Reynolds, Barbara Roggema, Harald Suermann and Mark Swanson.